Sindrom Makan Malam, Konsumsi Ultra-processed Foods, dan Aktivitas Fisik sebagai Faktor Risiko Gizi Lebih pada Mahasiswa Fakultas Ilmu Kesehatan UPN “Veteran” Jakarta: Night Eating Syndrome, Ultra-processed Foods Consumption, and Physical Activity as Risk Factors for Overnutrition in Students of Faculty of Health Science UPN “Veteran” Jakarta - Hanifa, Raishi Amatullah; Arini, Firlia Ayu; Wahyuningsih, Utami (Universitas Airlangga, 2024)
Background: Overnutrition among university students is a pressing concern, disrupting academic productivity and increasing the risk of metabolic diseases at a young age. According to RISKESDAS (2018), the prevalence of overweight/obesity among early adulthood populations reached 36%. Dietary patterns, unhealthy lifestyles, and night eating syndrome (NES) may contribute to overnutrition cases in university students. Objectives: This study aimed to investigate the association between night eating syndrome, ultra-processed food consumption, physical activity, and overnutrition among students at the Faculty of Health Science, UPN